Chemical stress assessment in large rivers using the average biomarker response approach with caged fish in situ: a case study on the Danube River in Novi Sad (Serbia) - Dina Tenji; Sonja Kaišarević; Bojana Mićić; Mirna Velki; Tobias Schulze; Martin Krauss; Muhammad Arslan Kamal Hashmi; Werner Brack; Ivana Teodorović (Environmental Sciences Europe)
Abstract Background Exposure assessment of aquatic biota to complex chemical mixtures from anthropogenic sources and evaluating potential impacts are crucial for mitigating toxic pressure and improving ecological status. The study focused on a section of the Danube River impacted by untreated municipal wastewater from the city of Novi Sad, Serbia, as well as partly treated industrial effluents and agricultural runoffs. This research aimed to implement average biomarker response (ABR) approach and use it as one of the multiple lines of evidence (LOE) to assess the ecological impact of pollution in complex scenarios, such as those in large rivers with multiple stressors. Results Cage-exposed specimens of native fish species, Cyprinus carpio, were analyzed for a wide range of biomarkers. Biomarker responses from caged fish were integrated with the biomarker responses of fish from wild populations of Abramis brama into an ABR value and interpreted using supporting evidence such as chemical analyses, effect-based methods and biomonitoring. Higher ABR values at pollution-impacted sites confirmed the presence of chronic toxic pressure caused by mixtures of chemicals at sublethal concentrations. Certain groups of biomarkers, such as those indicating neurotoxic effects, pointed to specific types of pollution confirmed by chemical analyses. Combined with other lines of evidence, ABR provided biologically plausible evidence of ecological impact of pollution at this hot spot and proved that pollution originating from the urban zone of the city of Novi Sad represents a significant pressure on the Danube ecosystem. Conclusions The integrated approach effectively assesses complex exposure scenarios in large rivers, evaluating pollution impact and underscoring the chronic toxic stress from anthropogenic sources. The assessment of biomarker responses in situ, whether based on caging experiments or sentinel biota, requires a comprehensive range of biomarkers and is overly resource-intensive for regular monitoring. Still, ecological relevance of the results justifies the efforts when the ecological impact of pollution needs to be assessed. ABR copes with high sample variability typical for in situ experiments, enables integration of inconsistent biomarker response patterns and facilitates the interpretation of the results and potentially wider acceptance of in situ tools in decision-making.